Genetic circuit modelling for improved synthetic biology design - Jeanny Putri Haliman (2013)
The advancement of synthetic biology lies heavily on key enabling technologies, one of which is the modeling of the synthetic gene behavior and its expressed protein. We identified the lacked of established model that mimic the correlation between synthetic gene expression and the host growth rate. To fill this information gap, we proposed two models which capable of accurately predict the synthetic circuit behavior at the pre-stationary phase. However, the increasing prominence of feedback system in the stationary phase required us to design more complex models.